Tinjauan Filosofis Egoisme dalam Komunikasi Politik di Era Pandemi Covid-19: Tantangan Kampanye Daring Pilkada Serentak Tahun 2020 di Indonesia - Eric Fernardo (UNIVERSITAS SARI MUTIARA INDONESIA, 2021)
Indonesia has held simultaneous regional elections on 9th December 2020. In contrast to previous years, when the campaign became a moment for citizens to gather with their prospective leaders, the Covid-19 pandemic forced the limitation of face-to-face meetings in order to implement Covid-19 health protocols. The government through the General Elections Commission (KPU) has issued General Election Commission Regulation (PKPU) 13/2020 which has explicitly encouraged candidate to use digital media in political campaigns. This is an effort to encourage candidates to take advantage of the digital space in campaigning. Currently, the candidates already have social media, but its use has not become the main information channel in political communication. During this campaign period, the candidates have used social media as a channel of political communication, but the social media used is limited to conveying invitations or information that the candidate has attended an activity, so social media has not become the main information channel in campaigning. The lack of organizing an online campaign by this candidate viewed from a philosophical perspective of egoism, based on the idea that the public or prospective voters are more focused on themselves. Participating in a online campaign for prospective voters requires extra sacrifices such as paying for internet quota fees, it is more troublesome because prospective voters have to learn to operate a online video application, and there are no direct benefits. The challenges faced in implementing an online campaign include, firstly, because it is preferred by the community, it is believed that the community prefers to meet face-to-face with the prospective leader directly because it provides direct benefits to the community, secondly, it is right on target because an online election campaign will not attract people, new voters because it will only be followed by voters who firmly support the candidate. Thirdly, because of the lack of creativity from the campaign team due to the lack of innovation from the candidates for not building a team that campaigns boldly, in addition to innovation, infrastructure problems that the evaluation of signal interference and the uneven distribution of digital infrastructure in the regions have hampered the implementation of bold campaigns.